ANALISIS EKONOMI USAHA MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) DI DESA TUNBAUN KECAMATAN AMARASI BARAT KABUPATEN KUPANG - Tomycho Olviana; Feni Yunita Tameno; Novi Theresia Klak (Universitas Udayana, 2024)
This study aims to explain how much income is obtained in the virgin coconut oil business by the FenaiBattun group, and explain the economic feasibility of virgin coconut oil business by the FenaiBattun group in Tunbaun Village, west Amarasi District, Kupang Regency. The data analysis used is quantitative data and qualitative data with data sources used, namely primary data and secondary data. To get the data the author conducted interviews, and documentation. The results of this study indicate that the analysis of the income received from the virgin coconut oil business by the FenaiBattun group in Tunbaun Village, West Amarasi District, Kupang Regency amounted to Rp 7,005,000/year. The R/C ratio value of the virgin coconut oil business is 2,84, which means that the FenaiBattun group’s virgin coconut oil business is profitale and feasible to operate. keyword: production, revenue, cost, virgin coconut oil, and business feasibility